Pattern of Common Bile Duct Injuries in Laparoscopic versus Open Cholecystectomy - Raza, Muhammad; Butt, Muhammad Qasim; Ashraf, Sohaib; Zain, Muhammad Ali; Haider, Faizan; Bhatti, Muhammad Waqas Ahmed (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the frequency of various patterns of injury to the common bile duct during laparoscopic versus open cholecystectomy. Study Design: Prospective longitudinal study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi Pakistan, from Sep 2023 to Mar 2024. Methodology: A total of 98 patients fulfilling the inclusion criteria were included in the study. All the patients underwent cholecystectomy either by laparoscopic or open procedure, and the procedure performed was also documented. Any case of injury to the CBD was documented, and its pattern, based on the Strasberg Classification, was assessed and documented. Results: Mean age was 45.23±6.85 years. 35(35.70%) were male, while 63(64.30%) were female. The mean body mass index was 32.50±2.85 kg/m2. The mean duration since diagnosis of gallstones was 7.45±1.18 months. 69(70.40%) had laparoscopic cholecystectomy, while 29(29.60%) had open cholecystectomy. The composite frequency of iatrogenic injury to the common bile duct (CBDI) was 7(7.10%). CBD injury occurred in 4(5.79%) in laparoscopic cholecystectomy, while in open cholecystectomy, it occurred in 3(10.34%), (p=0.425). In the laparoscopy Group, 2(2.89%) had Strasberg Class A injuries, and 2(2.89%) had Strasberg Class D injuries. In contrast, in the open procedure Group, 2(6.89%) had Strasberg Class D injuries, and 1(3.44%) had a Strasberg Class E injury. Conclusion: The CBD injury rate is lower with the laparoscopic approach of gallbladder removal and is associated with lesser severity of injury.